Pelatihan Bahasa Inggris untuk Tour Guide di Kelurahan Semarapura Kaja dalam Rangka Pengembangan Pariwisata Terintegrasi - Nyoman Sujaya (Linguistic Community Services Journal, 2021)
Currently, the activities of the Semarapura Kaja community are not optimizing due to the Covid-19 pandemic which is an obstacle to working as usual, one of which is the people in Klungkung Regency. The problem faced by the Semarapura Kaja community, namely the lack of English language skills among the youth of Semarapura Kaja village in the field of tourism as a tour guide. Lack of training or English teaching facilities both in terms of socialization and field practice, the solution offered and the purpose of holding community service activities is to carry out English training partnership program activities for tour guides in Semarapura Kaja Village to promote the tourist areas / services offered. The method used in this research is qualitative research through the interview stage to find out partner problems. Sources of data used in this study are primary data by conducting field observations to determine the problems faced by the local community. The results show that there is an increase in understanding the use of English for tour guides and being able to describe directions or tourist attractions in English.